2013
DOI: 10.1111/j.1365-2125.2012.04402.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of paracetamol and its metabolites in women at delivery and post‐partum

Abstract: AIMA recent report on intravenous (i.v.) paracetamol pharmacokinetics (PK) showed a higher total clearance in women at delivery compared with non-pregnant women. To describe the paracetamol metabolic and elimination routes involved in this increase in clearance, we performed a population PK analysis in women at delivery and post-partum in which the different pathways were considered. METHODSPopulation PK parameters using non-linear mixed effect modelling were estimated in a two-period PK study in women to whom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 28 publications
4
70
0
1
Order By: Relevance
“…This is in line with in vivo observations in humans, since compound-specific studies (e.g. lamotrigine, propofol and paracetamol, all undergoing glucuronidation) show raised metabolic drug clearance during pregnancy [6,7,8]. …”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…This is in line with in vivo observations in humans, since compound-specific studies (e.g. lamotrigine, propofol and paracetamol, all undergoing glucuronidation) show raised metabolic drug clearance during pregnancy [6,7,8]. …”
Section: Introductionsupporting
confidence: 60%
“…Physicians should be aware that the analgesic effect of paracetamol will be shorter in pregnant women or in any setting of raised estradiol levels. However, before higher paracetamol doses are considered to compensate for this, we would like to refer to the recently published evidence that the higher paracetamol clearance during pregnancy is due to a disproportional increase in glucuronidation clearance and a proportional increase in clearance of unchanged paracetamol and in oxidation clearance [7]. It is likely that the latter limits further dose increase in this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Paracetamol There are a number of paediatric popPK models for paracetamol published in the literature, which range from simple one compartment models to more complex three compartment models [31][32][33]. The model by Anderson et al [7], which contains the maturation function introduced in Equation [1], is a one compartment model.…”
Section: Bcs Class I Drugs (High Solubility High Permeability)mentioning
confidence: 99%
“…CYP2E1 plays a major role in metabolizing acetaminophen (a commonly used analgesic during pregnancy) to N-acetyl-p-benzoquinone, the toxic metabolite causing fatal liver injury (Lee et al, 1996). Of note, a recent study demonstrated that acetaminophen elimination to oxidative metabolites was significantly increased in women at delivery compared with that in postpartum women, suggesting clinically relevant increase in CYP2E1 expression and/or activity during pregnancy (Kulo et al, 2013). Taken together, caution should be advised when acetaminophen is prescribed to pregnant women.…”
Section: Discussionmentioning
confidence: 99%